2012
DOI: 10.1155/2012/948203
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis, Atherosclerosis, and Altered HDL Composition in Heme-Oxygenase-1-Knockout Mice

Abstract: To elucidate roles of heme oxygenase-1 (HO-1) in cardiovascular system, we have analyzed one-year-old HO-1-knockout mice. Homozygous HO-1-knockout mice had severe aortitis and coronary arteritis with mononuclear cellular infiltration and fatty streak formation even on a standard chow diet. Levels of plasma total cholesterol and HDL were similar among the three genotypes. However, homozygous HO-1-knockout mice had lower body weight and plasma triglyceride. HO-1-deficiency resulted in alteration of the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…41 HO-1 À / À mice generally have reduced body weight and are prone to develop vasculitis, atherosclerosis, anemia, and hepatic and renal iron accumulation, leading to tissue damage and chronic inflammation, along with organ injury/failure. 39,[42][43][44] HO-1 À / À mice typically die within the first 6 months. 44 Therefore, we decided to use HO-1 flox/flox mice that lack leukocytic HO-1 in this study to ensure that our results were not influenced by genetically caused illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…41 HO-1 À / À mice generally have reduced body weight and are prone to develop vasculitis, atherosclerosis, anemia, and hepatic and renal iron accumulation, leading to tissue damage and chronic inflammation, along with organ injury/failure. 39,[42][43][44] HO-1 À / À mice typically die within the first 6 months. 44 Therefore, we decided to use HO-1 flox/flox mice that lack leukocytic HO-1 in this study to ensure that our results were not influenced by genetically caused illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Using systemic manipulation of either HO-1 expression or activity, some studies suggested that HO-1 plays a vital role in atherosclerosis initiation and development. HO-1-null mice show a noteworthy increase in plasma lipid hydroperoxides [ 44 ]. Similarly, rabbits treated with SnPP, an HO-1 inhibitor, exhibit a significant lipid deposits in abdominal aortic plaques [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-atherogenic role of HO-1 has been reported in various studies. Pharmacological inhibition or knockdown of HO-1 show significant increases in lesion formation and further accelerates atherosclerosis in ApoE null mice [ 51 ], Watanabe heritable hyperlipidemic rabbits (WHHL) [ 52 ] and aortitis in chow-fed old C57BL/6 mice [ 53 ]. Apart from that, it has been demonstrated that upregulation of HO-1 genes expression by intraventricular administration of AdProT in mice has the capability to attenuate the development of atherosclerosis by reducing macrophages infiltration [ 54 ].…”
Section: Nrf2 and Macrophage Foam Cells Formationmentioning
confidence: 99%